Pemanfaatan Program Microsoft Mathematics untuk Meningkatkan Hasil Belajar Matematika Siswa - Nur Hidayati Miftahul Jannah; Sudianto Sudianto (Papanda Publisher, 2025)
Mathematics learning often faces obstacles in the form of low student learning outcomes due to difficulty understanding abstract concepts. The use of learning technology is an alternative to overcome this problem. One software that can be used is the Microsoft Mathematics program which provides visualization features and step-by-step problem solving. This research aims to systematically examine the use of the Microsoft Mathematics program in improving student learning outcomes in mathematics learning. The research method used is a Systematic Literature Review by reviewing relevant scientific articles published in the period 2015 to 2025. The review process includes searching, selecting and analyzing articles based on predetermined inclusion and exclusion criteria. The results of the study show that the use of Microsoft Mathematics consistently provides positive impact on student learning outcomes, conceptual understanding, problem solving abilities, and learning motivation at various levels of education. Apart from that, this program also helps teachers deliver mathematics material more effectively and efficiently. The conclusion of this research shows that Microsoft Mathematics is an effective and potential learning media for improving student learning outcomes in mathematics learning.